Pokok-pokok pikiran lepas formulasi Undang-Undang no. 22 dan 25 tahun 1999 dan dampak terhadap kebijakan publik = Main ideas of the government regulation no. 22 and 25, 1999 and their effects on public policy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The New Order has caused centralized authority and poor initiative from the local authority. The government had too big power and this resulted in the imhalance of power sharing between the government and local authority. Autonomy is still considered as rig. The new law on autonomy launched in 1999 is seen as tendencious and ambitious. This is the result of poor implementation in the local authority. What arc demanded by local authority is actually more power sharing. more just income distribution. and independent management system in which the local authority's administration is expected to he concrete. transparent. and independent.